2012
DOI: 10.1093/jac/dks019
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, species distribution and in vitro antifungal susceptibility of fungaemia in a Spanish multicentre prospective survey

Abstract: Fungaemia is more common in non-critical patients. C. albicans is the most common species, followed by C. parapsilosis and C. glabrata. Nearly 90% of yeasts are susceptible to all antifungal agents tested. Resistance rates change moderately when applying the new SSCBPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
68
5
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(91 citation statements)
references
References 15 publications
11
68
5
7
Order By: Relevance
“…Candida species remain a major cause of IFIs, resulting in significant morbidity and mortality in health care settings (1,3,4). Moreover, the number of candidemia cases caused by non-albicans Candida species has been increasing in recent years (5)(6)(7). It is known that the treatment of some Candida species is difficult because of their innate or acquired resistance to antifungal agents (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Candida species remain a major cause of IFIs, resulting in significant morbidity and mortality in health care settings (1,3,4). Moreover, the number of candidemia cases caused by non-albicans Candida species has been increasing in recent years (5)(6)(7). It is known that the treatment of some Candida species is difficult because of their innate or acquired resistance to antifungal agents (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification (ID) and antifungal resistance testing of these organisms are important for guiding therapy and determining prognosis in these IFIs, as well as in epidemiologic surveys (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). One of the most important aspects of global and regional surveillance programs is to use stateof-the-art methods for ID and antifungal resistance testing of the organisms that are implicated in IFIs (2, 6-8, 11, 13).…”
mentioning
confidence: 99%
“…Antifungal susceptibility testing has departed from a "one breakpoint fits all" approach (15,34,35) to using more-refined species-specific CBPs at the shorter 24-h reporting times (11,12,29). The recent surveillance focus has been on how best to detect the emergence of resistance within a population of a given fungal species (2,7,8,(12)(13)(14)36). The development of epidemiological cutoff values (ECVs) has aided in the detection of non-WT strains in given populations, allowing a more focused approach to the molecular definition of strains presenting less-susceptible profiles (6,8,11,13,33,37).…”
mentioning
confidence: 99%
“…Together with Candida albicans, the species most frequently isolated from clinical specimens (4, 5), other yeast species are increasingly recovered from patients with well-documented infections (6-8). They encompass non-albicans Candida species, including the rarer species Candida famata, Candida kefyr, Candida lipolytica, Candida rugosa, and Candida utilis, as well as uncommon species belonging to the genera Trichosporon, Rhodotorula, Pichia, Malassezia, and Saccharomyces (3).It was recently observed that some yeast species are highly virulent and show reduced susceptibility to one or several antifungal agents (2,3,(8)(9)(10)(11)(12) and that this has important clinical repercussions, often resulting in therapeutic failures (6, 13-15). Thus, accurate identification of these species is of utmost importance (16), but this goal is difficult to achieve, at least using conventional phenotypic methods (17,18).…”
mentioning
confidence: 99%